Effects of a time-varying strong magnetic field on transient increase in Ca2+ release induced by cytosolic Ca2+ in cultured pheochromocytoma cells - Ikehara, Toshitaka; Yamaguchi, Hisao; Hosokawa, Keiko; Houchi, Hitoshi; Park, Ki Ho; Minakuchi, Kazuo; Kashimoto, Hideki; Kitamura, Mitsuo; Kinouchi, Yohsuke; Yoshizaki, Kazuo; Miyamoto, Hiroshi (Biochimica et biophysica acta, 2005)
Exposure of pheochromocytoma (PC 12) cells to a time-varying 1.51 T magnetic field inhibited an increase in the intracellular Ca2+ concentration ([Ca2+]i) induced by addition of caffeine to Ca(2+)-free medium. This inhibition occurred after a 15-min exposure and was maintained for at least 2 h. [Ca2+]i sharply increased in cells loaded with cyclic ADP-ribose, and 2-h exposure significantly suppressed the increase. Addition of ATP induced a transient increase in intracellular Ca2+ release mediated by IP3 receptor, and this increase was strongly inhibited by the exposure. Results indicated that the magnetic field exposure strongly inhibited Ca2+ release mediated by both IP3 and ryanodine receptors in PC 12 cells. However, thapsigargin-induced Ca2+ influx (capacitative Ca2+ entry) across the cell membrane was unaffected. The ATP content was maintained at the normal level during the 2-h exposure, suggesting that ATP hydrolysis was unchanged. Therefore, Mg2+ which is known to be released by ATP hydrolysis and inhibit intracellular Ca2+ release may not relate the exposure-caused inhibition. Eddy currents induced in culture medium appear to change cell membrane properties and indirectly inhibit Ca2+ release from endoplasmic reticulum and other Ca2+ stores in PC 12 cells.